2006
DOI: 10.1073/pnas.0509724103
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic independence of mouse measures of some aspects of novelty seeking

Abstract: High novelty seeking is a complex personality attribute correlated with risk for substance abuse. There are many putative mouse models of some aspects of novelty seeking, but little is known of genetic similarities among these models. To assess the genetic coherence of “novelty seeking,” we compared the performance of 14 inbred strains of mice in five tests: activity in a novel environment, novel environment preference, head dipping on a hole-board, object preference, and a two-trial version of the spontaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 36 publications
3
53
0
Order By: Relevance
“…Previous work has shown that inbred mouse strains are characterized by different levels of head dipping in hole-board tasks [32,54]. Pharmacological assays have indicated that numbers of head dips can be increased by treatment with diazepam or other anxiolytic drugs, and decreased by anxiogenic compounds [75], although these changes may be related to general drug effects on activity levels [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that inbred mouse strains are characterized by different levels of head dipping in hole-board tasks [32,54]. Pharmacological assays have indicated that numbers of head dips can be increased by treatment with diazepam or other anxiolytic drugs, and decreased by anxiogenic compounds [75], although these changes may be related to general drug effects on activity levels [33].…”
Section: Discussionmentioning
confidence: 99%
“…We needed to find an optimal way to present up to 16 measures per test in a graphic form. In addition, as shown in Results, inbred mouse strains can have very different levels of nose poke responses (see also [32,54]), yet it would be beneficial to present the patterns of hole preference in a way that was comparable across strains or experimental groups. One way to control for the differences in numbers of nose pokes was to present the data as percent of total nose pokes per hole for each experimental group.…”
Section: Data Presentationmentioning
confidence: 99%
“…In a third test of anxiety-like behavior, the light-dark exploration test, the small and medium BLA groups spent less time in the light compartment and made fewer light-dark intercompartment transitions than the large BLA group. Different mouse tests for anxiety likely measure different forms of behavior controlled by distinct genetic factors (Turri et al, 1999;Holmes et al, 2003;Kliethermes and Crabbe, 2006) and it is possible that the profile of the small and medium BLA groups in the light-dark exploration test reflects a high anxiety-like phenotype that is not seen in the other tests. Taken together however, the differences between BLA volume groups on the anxiety-related assays (particularly the open-field and light-dark exploration tests) were marginal and are most parsimoniously interpreted as modest locomotor inhibition in response to novelty rather than a clear high anxiety-like phenotype in mice with smaller BLA volumes.…”
Section: Discussionmentioning
confidence: 99%
“…Investigating this is particularly challenging, as there are no pharmacological treatments known to fully dissociate changes in overall locomotor speed from the development of route-tracing stereotypies (e.g., Griebel et al 2000;Kliethermes and Crabbe 2006;Ohl et al 2001). As per the rationale described in "Materials and methods," we chose to mathematically transform home-cage data to normalize locomotor speeds without altering mouse locomotor paths.…”
Section: Route-tracing Stereotypy Scores Are Not Correlated With Overmentioning
confidence: 99%